Respostas

2013-10-11T07:24:25-03:00
|3x+1|=|x-5| 1)            3x + 1 = x - 5              3x – x = -5 – 1              2x = -6                x = -6/2                x = -3   3x + 1  = -x + 5 3x + x = 5 – 1 4x = 4 x = 1 2)            -3x – 1 = -x + 5              -3x + x = 5 + 1              -2x = 6                 x = -3

-3x -1 = -x – 5 -3x + x = -5 + 1 -2x = -4 X = 2
 

  1)            2x -3x+ 1 = 1              2x -3x+ 1 - 1      = 0              2x -3x = 0              x(2x -3) = 0              x’ = 0                x” = 2x – 3 = 0                     2 x” – 3 =0                        x” = 3/2         S = { 0, 3/2}           2)            -2x + 3x -1= 1                        -2x + 3x -1= 1      (-1)  -2x + 3x -1 - 1 = 0            2x - 3x  + 2 = 0           3 ± √9 – 4. 2. 2)                  2.(-2)                  x’ = 3 -  ...  є/  R { }  

|4-3x|=3x-4
4-3x=3x-4 -6x = 0    x = 0    V = { 0 } -4 + 3x=3x-4 0x - -4 + 4   impossível!    
2 3 2